The Analysis of Leadership, Motivation, and Work Environment on Employee Performance at Pt. Medan Distribusindo Raya - Pratama, Siswa; Andika, Rindi; Suwarno, Suwarno; Ramadhani, Syahrul (Jurusan Sejarah, Seni, dan Arkeologi, FKIP, Universitas Jambi, 2024)
This study aimed to examine the Analysis of Leadership, Work Motivation, and Work Environment on Employee Performance of PT Medan Distribusindo Raya, especially in the Marketing and Sale section, both partially and simultaneously. This research used quantitative methods with data collection using the Likert scale method. The subjects used in this study were 90 employees of PT Medan Distribusindo Raya in the Marketing and Sale position and were taken using total sampling. The results of this study indicated that first, leadership has a positive and significant effect on employee performance.